Early menopause and premature ovarian insufficiency: problems and perspectives - D. V. Blinov; P. L. Hasan; A. N. Mnatsakanyan; D. I. Korabelnikov; A. T. Safarov; N. V. Pavlova; N. S. Zakharova; D. A. Ponomarev; D. A. Petrenko (Акушерство, гинекология и репродукция)
In this review we summarize current data on prevalence, etiology and pathogenesis resulting in premature ovarian insufficiency (POI). In particular, genetic, autoimmune, metabolic, iatrogenic disorders as well as unfavorable impact of environmental factors represent key pathogenetic mechanisms underlying POI development. Clinical picture of this disease is mainly manifested by oligo- and amenorrhea as well as genitourinary menopausal syndrome (GUMS). Special attention is paid to a link between such clinical signs and psychosocial discomfort not being a life-threatening condition but still able to markedly lower quality of woman’s life and considered as a comorbidity with type 2 diabetes mellitus, osteoporosis and cardiovascular diseases. Hormone replacement therapy (HRT) serves as the first-line therapeutic approach for treating POI, which is performed according to the principles similar to those used to perform menopausal hormone therapy (MHT) in case of natural menopause that should be continued until reaching at least the average age for the onset of menopause. Topical estriol therapy eliminates GUMS symptoms, which in turn positively affects sexual function and woman’s psychosocial status and contributes to improved quality of life. The data from recent studies examining topical estriol therapy in POI demonstrated high efficacy and safety. Finally, we also discuss diverse strategies to support reproductive function in women with POI.